Varied diets: implications for lamb performance, rumen characteristics, total antioxidant status, and welfare. (11th November 2021) - Garrett, Konagh; Beck, Matthew R; Marshall, Cameron J; Maxwell, Thomas M R; Logan, Chris M; Greer, Andrew W; Gregorini, Pablo
Abstract: Intensive pastoral systems have moved away from diverse and varied diets towards overly simple monotonous diets. Feed choice through time is an obsolete way of providing forage to animals, as intensive management schemes generally allocate a single herbage or a dyad mixed sward. Monotonous feeding regimes impose nutritional repetition, which may impair animal performance and welfare. The objective of this experiment was to determine the impact of a diverse diet [DIV; free choice from perennial ryegrass ( Lolium perenne L.), plantain ( Plantago lanceolata L.), alfalfa ( Medicago sativa L.), and chicory ( Cichorium intybus L.) at all times], a varied diet [VAR; choice from ryegrass and plantain in the AM (0700–1600 h), and chicory and alfalfa in PM (1600–0700 h)], and a single forage diet of alfalfa [SFA; alfalfa at all times], on DMI, performance, and welfare of lambs. Six-month-old Coopworth ram lambs ( n = 21) were offered their respective fresh-forage treatment ( n = 7) diet indoors for 20 d. The DIV lambs consumed 1.64 ± 0.03 kg DM/d (mean ± SEm), which was 6% more ( P < 0.05; 1.54 ± 0.03 kg DM/d) than the SFA and were not different ( P > 0.05; 1.59 ± 0.03 kg DM/d) to the VAR lambs. Average daily gain (ADG) of DIV (296 g/d) and VAR (378 g/d) was 30% and 67% greater ( P < 0.05) than that in the SFA lambs (227 g/d), respectively. The VAR lambs had 28% greater ( P < 0.05) ADG than the DIV lambs. Differences among treatments were detected ( P < 0.05) for the proportion of the day spent conducting the following behaviors: eating, ruminating, idling, lying, and standing. In addition, the number of bouts of stereotypic behaviors recorded from the SFA lambs (13.2 ± 2.2) was 150% greater ( P < 0.05) than the DIV (5.1 ± 1.0) and VAR (5.5 ± 1.0) lambs. Our results suggest that the varied diet offered can improve animal performance and welfare compared to a monotonous SFA diet. Feeding management to provide a varied diet can improve performance relative to giving lambs free choice from taxonomically diverse forage options. Moreover, performance is affected by more than the primary chemical composition of the diet consumed, but how the diet is presented through time and the herbage species and quantities of each that are consumed to reach that chemical composition.